The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/nss.s48970
|View full text |Cite
|
Sign up to set email alerts
|

Total sleep time obtained from actigraphy versus sleep logs in an academic sleep center and impact on further sleep testing

Abstract: BackgroundWhile actigraphy has been deemed ideal for the longitudinal assessment of total sleep time (TST) by select groups, endorsement has not been universal and reimbursement is lacking, preventing its widespread use in clinical practice. This study compares longitudinal TST data obtained by actigraphy and logs preceding a clinical evaluation, and secondarily ascertains whether longitudinal TST impacts clinicians’ decisions to proceed with further sleep testing.MethodsThis was a retrospective, consecutive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We first assessed the level of agreement between actigraphy and sleep logs for estimating variables related to sleep and wake states, expecting some level of consistency between the two methods [ 29 , 36 ], but also hypothesizing potential individual differences [ 38 ] across the different types of sleep metrics [ 39 ]. Second, we examined task compliance in terms of submitting sleep logs daily according to experimental instructions, expecting that compliance would tend to worsen over time [ 40 , 41 ], but also hypothesizing individual differences in the ability of participants to sustain motivation and achieve strict compliance for four consecutive months. Last we examined the relationship between compliance and agreement, evaluating whether individuals showing higher compliance also tended to produce higher fidelity subjective estimates of their sleep with reference to objective actigraph measurements.…”
Section: Introductionmentioning
confidence: 99%
“…We first assessed the level of agreement between actigraphy and sleep logs for estimating variables related to sleep and wake states, expecting some level of consistency between the two methods [ 29 , 36 ], but also hypothesizing potential individual differences [ 38 ] across the different types of sleep metrics [ 39 ]. Second, we examined task compliance in terms of submitting sleep logs daily according to experimental instructions, expecting that compliance would tend to worsen over time [ 40 , 41 ], but also hypothesizing individual differences in the ability of participants to sustain motivation and achieve strict compliance for four consecutive months. Last we examined the relationship between compliance and agreement, evaluating whether individuals showing higher compliance also tended to produce higher fidelity subjective estimates of their sleep with reference to objective actigraph measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Actigraphy was used as a validated method to collect sleep data in the ambulatory environment to provide a more precise estimate of sleep duration than self-report. 28, 29 Additionally, we conducted an exploratory analysis to determine the impact of habitual sleep duration on the number of oocytes retrieved, an important clinical outcome in IVF and a measure associated with the ultimate goal of live birth. 30 …”
Section: Introductionmentioning
confidence: 99%
“…The correlations between selfreported sleep characteristics and those from actigraphy are uniformly higher than with respect to PSG, albeit not strong. Several studies on adult participants have shown moderate correlations between an individual's self-reported and actigraphy-derived measure of sleep duration, with most participants tending to overestimate their own sleep duration in comparison to actigraphy (r's =.34-.57; Auger, Varghese, Silber, & Slocumb, 2013;Lauderdale, Knutson, Yan, Liu, & Rathouz, 2008;Lockley, Skene, & Arendt, 1999;McCall & McCall, 2012;Tomita et al, 2013). One study estimated that among healthy adults, 34% of participants reported sleep durations that deviated ±1 hour from actigraphy-derived duration, with most of self-report durations being longer than the actigraphy measure (Van Den Berg et al, 2008).…”
Section: Sleep Assessmentsmentioning
confidence: 99%